S2k guideline: Laser therapy of the skin. (13th September 2022) - Paasch, Uwe; Zidane, Miriam; Baron, Jens Malte; Bund, Thorsten; Cappius, Hans‐Joachim; Drosner, Michael; Feise, Konstantin; Fischer, Tanja; Gauglitz, Gerd; Gerber, Peter Arne; Grunewald, Sonja; Herberger, Katharina; et al.
Summary: This guideline aims to improve the efficiency and safety of lasers and optical radiation sources with similar effects (especially IPL). Laser therapy of skin lesions with an increased amount of melanocytes should be performed with caution. Laser treatment of pigmented melanocytic nevi is not recommended. The guideline contains recommendations regarding the treatment of lentigines and café‐au‐lait spots, non‐pigmented dermal nevi, Becker nevus, nevus of Ota/Hori/Ito and melasma. Further recommendations focus on the treatment of skin lesions without an increased amount of melanocytes (ephelides, postinflammatory hyperpigmentation including berloque dermatitis, seborrheic keratoses, traumatic/decorative tattoos and metallic deposits), hypopigmentation (vitiligo), benign non‐pigmented neoplasms (fibrous papule of the nose, nevus sebaceus, epidermal nevus, neurofibroma, sebaceous gland hyperplasia, syringoma, xanthelasma palpebrarum), inflammatory dermatoses (acne papulopustulosa/conglobata, acne inversa, granuloma faciale, lichen sclerosus, lupus erythematosus, psoriasis vulgaris, rosacea, rhinophyma), wrinkles/dermatochalasis/striae, hypertrichosis, scars (atrophic, hypertrophic; keloids, burn/scald scars), laser‐assisted skin healing, onychomycosis, precancerous lesions and malignant tumors (actinic keratoses/field cancerization, cheilitis actinica, basal cell carcinoma), vascular skin lesions (angiokeratoma, angioma, hemangioma, malformation, spider veins, granuloma telangiectaticum (pyogenic granuloma), rubeosis (erythrosis interfollicularis colli, ulerythema ophryogenes), nevus flammeus, telangiectasias and Osler's disease (hereditary hemorrhagic telangiectasia) and viral skin lesions (condylomata acuminata, mollusca contagiosa, verrucae planae juveniles/vulgares/ verrucae palmares et plantares).